Inferring the mating system in the burrowing shrimp Lepidophthalmus bocourti (Decapoda, Axiidea, Callichiridae) from the social structure and sexual dimorphism - Hernáez, Patricio; Villegas-Castro, Erick; João, Marcio Camargo Araujo [UNESP]; Duarte, Rafael Campos; Rivadeneira, Marcelo M. (Springer Nature, 2021)
Abstract: Most burrowing shrimps (infraorder Axiidea and Gebiidea) are characterized by solitary habits, which led many of these species to evolve a remarkable sexual dimorphism both in body size and chelipeds because of sexual selection. Given that monogamous species are known to live in heterosexual pairs and exhibit a low degree of sexual dimorphism, it is expected that burrowing shrimps are not monogamous. We tested this hypothesis using the burrowing shrimp Lepidophthalmus bocourti as a model. Against expectations, shrimps were found living not only individually but also in homosexual and heterosexual pairs and trios within their respective burrows. The social structure in L. bocourti seemed to be an ontogenetically defined strategy, since most solitary individuals were juveniles of both sexes, while the heterosexual combinations were composed by adult shrimps. Sex distribution of pairs and trios suggested that female-female and male-female-female associations might be stable over time. Only 7% of the inhabited burrows were occupied by a heterosexual pair, and ovigerous females were found dwelling either in solitary or in heterosexual combinations, indicating that this species is not monogamous. Most of the male-female associations occurring both in pairs and trios were dominated by females larger than males. We observed sexual dimorphism in the size of the major cheliped, being larger in males than in females. Ontogenetic pattern of burrow occupation allied to considerable sexual dimorphism argue in favour that L. bocourti is not monogamous and suggest that the major cheliped might have an important role during the male-male competition for receptive females. Significance statement: Burrowing shrimps (Axiidea and Gebiidea) are characterized by their solitary habits and by marked sexual dimorphism both in body size and chelipeds. The way these shrimps occupy their burrows and how common sexual dimorphism occurs remains unknown for most species. This is particularly important since the predominance of certain mating system (i.e. monogamous versus polygamous) can be inferred from the social structure and morphological differences of characters among the sexes of a species. We described the burrow use pattern and sexual dimorphism of the burrowing shrimp Lepidophthalmus bocourti to infer the mating system in this species. L. bocourti showed a complex social structure composed of both solitary shrimps and homosexual and heterosexual pairs and trios of shrimps. This burrow use pattern is allied with sexual dimorphism both in body (when it came to male-female associations) and in cheliped size.
Keywords: Allometric growth; Axiidea; Burrow occupation; Costa Rica; Crustacea; Mating systems